Fixing Flexner: Disrupting and Rebuilding Academic Medicine for Women of Color to Lead - Chelsea Dorsey; Vineet M Arora; Keme Carter (JMIR Publications, 2023)
In an effort to address the lack of compositional diversity seen in academic leadership, our generation has an opportunity to rebuild academic medicine in a way that welcomes, values, and supports the development and success of women of color.